Arbitragem no setor de energia elétrica - Ribeiro, Diogo Albaneze Gomes (2015)
This study aims to investigate the use of arbitration in contracts executed in the electric power sector, analyzing not only their pertinence, but, principally, their effective application in generation, distribution, transmission, and commercialization contracts of electricity. The industry, after going through a process of unbundling, that distinguished the monopolized activities likely to be provided for in the/a competition regime, underwent major innovations introduced by Law 9.648/1998 (that created the independent electricity producer and made commercialization an autonomous activity). As a result of these innovations, the contractual relationship between the actors of the sector multiplied, turning it into one of the most complex regulated markets and, consequently, propitious to the use of alternative mechanisms for conflict resolution, including arbitration. In this context, the use of mediation, conciliation, and arbitration institutes came to be expressly provided for in various industry standards, and, in some situations, mandatory use as in the commercialization of electricity. For these reasons, arbitration in the electricity sector is turning into a field that, increasingly, deserves attention from the arbitration community